Essays on international prices and the subjacent market structure - Barroso, João Barata Ribeiro Blanco (2010)
The thesis uses international price data to identify parameters of trade models with imperfect competition, therefore allowing inference on exchange rate behavior, gains from trade and variety of domestic goods. First, we investigate Brazilian exporters pricing behavior over the long-run following destination specific exchange rate shocks. We find evidence of incomplete exchange-rate pass-through in the long-run, which supports the market structure explanations over short-run sticky-price explanations. Second, we calculate import price indexes and the implied welfare gains from new varieties of imported goods, based on disaggregated estimates of elasticity of substitution parameters. Finally, we qualify standard results in the literature that point to a reduction in domestic varieties after trade liberalization; domestic varieties may expand if we introduce an additional margin in firms‟ technology, such as intermediate goods or high skilled labor.